A randomised controlled trial of the clinical effectiveness and cost-effectiveness of different knee prostheses: the Knee Arthroplasty Trial (KAT). - Murray, D; MacLennan, G; Breeman, S; Dakin, H; Johnston, L; Campbell, M; Gray, A; Fiddian, N; Fitzpatrick, R; Morris, R; Grant, A (NIHR Health Technology Assessment Programme, 2014)
BACKGROUND: In the late 1990s, new developments in knee replacement were identified as a priority for research within the NHS. The newer forms of arthroplasty were more expensive and information was needed on their safety and cost-effectiveness. OBJECTIVES: The Knee Arthroplasty Trial examined the clinical effectiveness and cost-effectiveness of four aspects of knee replacement surgery: patellar resurfacing, mobile bearings, all-polyethylene tibial components and unicompartmental replacement. DESIGN: This study comprised a partial factorial, pragmatic, multicentre randomised controlled trial with a trial-based cost-utility analysis which was conducted from the perspective of the NHS and the patients treated. Allocation was computer generated in a 1 : 1 ratio using a central system, stratified by eligible comparisons and surgeon, minimised by participant age, gender and site of disease. Surgeons were not blinded to allocated procedures. Participants were unblinded if they requested to know the prosthesis they received. SETTING: The setting for the trial was UK secondary care. PARTICIPANTS: Patients were eligible for inclusion if a decision had been made for them to have primary knee replacement surgery. Patients were recruited to comparisons for which the surgeon was in equipoise about which type of operation was most suitable. INTERVENTIONS: Patients were randomised to receive a knee replacement with the following: patellar resurfacing or no patellar resurfacing irrespective of the design of the prosthesis used; a mobile bearing between the tibial and femoral components or a bearing fixed to the tibial component; a tibial component made of either only high-density polyethylene ('all polyethylene') or a polyethylene bearing fixed to a metal backing plate with attached stem; or unicompartmental or total knee replacement. MAIN OUTCOME MEASURES: The primary outcome was the Oxford Knee Score (OKS). Other outcomes were Short Form 12; EuroQol 5D; intraoperative and postoperative complications; additional surgery; cost; and cost-effectiveness. Patients were followed up for a median of 10 years; the economic evaluation took a 10-year time horizon, discounting costs and quality-adjusted life-years (QALYs) at 3.5% per annum. RESULTS: A total of 116 surgeons in 34 centres participated and 2352 participants were randomised: 1715 in patellar resurfacing; 539 in mobile bearing; 409 in all-polyethylene tibial component; and 34 in the unicompartmental comparisons. Of those randomised, 345 were randomised to two comparisons. We can be more than 95% confident that patellar resurfacing is cost-effective, despite there being no significant difference in clinical outcomes, because of increased QALYs [0.187; 95% confidence interval (CI) -0.025 to 0.399] and reduced costs (-£104; 95% CI -£630 to £423). We found no definite advantage or disadvantage of mobile bearings in OKS, quality of life, reoperation and revision rates or cost-effectiveness. We found improved functional results for metal-backed tibias: complication, reoperation and revision rates were similar. The metal-backed tibia was cost-effective (particularly in the elderly), costing £35 per QALY gained. CONCLUSIONS: The results provide evidence to support the routine resurfacing of the patella and the use of metal-backed tibial components even in the elderly. Further follow-up is required to assess the stability of these findings over time and to inform the decision between mobile and fixed bearings. TRIAL REGISTRATION: Current Controlled Trials ISRCTN45837371. FUNDING: This project was funded by the NIHR Health Technology Assessment programme and the orthopaedic industry. It will be published in full in Health Technology Assessment; Vol. 18, No. 19. See the NIHR Journals Library website for further project information.